The queen's secret - George, Jessica Day, 1976- (George, Jessica Day, 1976- Rose legacy novel., 2019)
When a deadly disease breaks out, it is up to Anthea and her friends in the Horse Brigade to transport medicine throughout the kingdom while avoiding Anthea's evil mother and uncovering a powerful secret.